2007
DOI: 10.1039/b706302b
|View full text |Cite
|
Sign up to set email alerts
|

POP exposure from fish liver consumption and risk of cancer—the Norwegian Women and Cancer Study

Abstract: The aim of the study was to investigate the hypothesis that consumption of fish liver increases cancer risk in humans due to increased intake of persistent organic pollutants (POPs). This study is based on data from the Norwegian Women and Cancer Study (NOWAC). The study has a prospective cohort design with questionnaire data from 64 285 randomly selected Norwegian women (aged 40-70 at baseline) and linkage to the Norwegian Cancer Registry. Cox proportional hazards regression was used to calculate risk ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
(39 reference statements)
0
7
0
1
Order By: Relevance
“…Consumption of fillet without the skin can help to significantly reduce PFAS uptake. The consumption of fish liver should also be avoided when the contamination with PFASs cannot be excluded [43]. As shown in the present study, liver can contain up to 24% of the total body burden of single PFASs, despite the low organ weight, due to high tissue concentrations.…”
Section: Proportional Distribution Of Pfas Whole-body Burdenmentioning
confidence: 61%
“…Consumption of fillet without the skin can help to significantly reduce PFAS uptake. The consumption of fish liver should also be avoided when the contamination with PFASs cannot be excluded [43]. As shown in the present study, liver can contain up to 24% of the total body burden of single PFASs, despite the low organ weight, due to high tissue concentrations.…”
Section: Proportional Distribution Of Pfas Whole-body Burdenmentioning
confidence: 61%
“…A study of women from New York City found no apparent association between fish intake and breast cancer risk [12,14,21]. Consistent with this, a large-scale EPIC study [10], and studies conducted in Norway [22] and Sweden [23] found no apparent evidence for an association between fish intake and breast cancer risk. Holmes et al .…”
Section: Discussionmentioning
confidence: 85%
“…However, demonstrating the effects of large-scale contamination on human populations is not straightforward (Eisler 2003), and epidemiological studies are often confounded by other health effects in the population (Brustad et al 2007). Where there are discrete pathways, e.g.…”
Section: Terrestrial Exposurementioning
confidence: 99%